The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/inr.12402
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities for specialized nursing practice in the United Arab Emirates

Abstract: The findings provide guidance on key areas for nurses to focus research contributions to enhance evidence-based care and strengthen health systems. The identified priorities may also guide researchers in academic institutions to conduct research informed by current, clinically relevant issues. The findings may help inform funders and policymakers to support allocation of funding to research that has potential to contribute to enhancing nursing care in specialist areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The result of this study and the previous study, which reviewed the current research status (McCreaddie et al., 2018) and the priorities of nursing research in UAE (Al-Yateem et al., 2016, 2018, 2019), form the basis of the future UAE Nursing and Midwifery Council nursing research strategy. The Subcommittee looks forward to reporting on future initiatives to ensure the nursing profession continues to influence and enhance health care policy and practice in the UAE.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The result of this study and the previous study, which reviewed the current research status (McCreaddie et al., 2018) and the priorities of nursing research in UAE (Al-Yateem et al., 2016, 2018, 2019), form the basis of the future UAE Nursing and Midwifery Council nursing research strategy. The Subcommittee looks forward to reporting on future initiatives to ensure the nursing profession continues to influence and enhance health care policy and practice in the UAE.…”
Section: Resultsmentioning
confidence: 86%
“…Finally, this study in highlighting the barriers to research identified by study participants has added great value to the previous studies done in the UAE about nursing research. To conclude, having identified the current status of nursing research in UAE (McCreaddie et al., 2018), the barriers to conduct and utilize research, and the priorities of nursing research in UAE (Al-Yateem et al., 2018, 2019), the stage is set to work out a strategy to move the nursing research agenda forward in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of this development has included major investment in hospitals, medical centres and trauma units. There is an accompanying emphasis on professional and research-driven practice (Al-Yateem et al, 2018), though some regulatory, social and institutional barriers remain to providing advanced specialist RN services (Brehens, 2018).…”
Section: The Uae Contextmentioning
confidence: 99%
“…Part of this development has included major investment in hospitals, medical centres and trauma units. There is an accompanying emphasis on professional and research‐driven practice (Al‐Yateem et al, ), though some regulatory, social and institutional barriers remain to providing advanced specialist RN services (Brehens, ). Accordingly, there is ongoing investment in improving successful completion of national licensing examinations for local nurses (Brownie, Williams, et al, ), including development of specialty skills (Brownie, Hunter, Aqtash, & Day, ).…”
Section: Introductionmentioning
confidence: 99%